Knowledge of mothers regarding prevention of child abuse - Pappachan C, Binsha; Philip, Jipsa; Pinto, Jenita; Aleyamma Kurian, Nikeetta; Rufina Rodrigues, Victoria (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: In this study assess the knowledge of mothers regarding the prevention of child abuse, find association between the knowledge of mothers and selected baseline data. The World Health Organization (WHO) distinguishes four types of child abuse i.e., physical abuse, sexual abuse, emotional, psychological abuse, and neglect. Method: In this study the population was the mothers of children with 1-14 years of age in Father Muller Medical College, Mangalore. In India, an estimated 679,000 children were victims of abuse and neglect as per the 2013 statistics. Result: Analysis of demographic variables shows that highest (35%)of the mothers are in the age group of 26-30 years and about 24% of them were in the age group of 31-35 years. Majorities (44%) of the mothers were with 2 children, 41% of the mothers with 1 child, and only 2% mothers with more than 3 children. Among the group majority (52%) of the mothers were having 1 male child and 55% were having one female child. The data also showed that 47%of them have at least one child below 14 years. Conclusion: The study findings revealed that most of the mothers (60%) had excellent knowledge regarding prevention of child abuse, about (34%) of them had good knowledge, about (6%) had average knowledge and none of the mothers had poor knowledge.